Impact of long‐acting octreotide in patients with early‐stage MEN1‐related duodeno‐pancreatic neuroendocrine tumours. (19th February 2014) - Ramundo, V.; Del Prete, M.; Marotta, V.; Marciello, F.; Camera, L.; Napolitano, V.; De Luca, L.; Circelli, L.; Colantuoni, V.; Di Sarno, A.; Carratù, A. C.; de, C.; et al.
Summary Background Somatostatin analogues (SSA) represent one of the main therapeutic option in patients affected with functioning well‐differentiated neuroendocrine tumours (NETs). There are no studies specifically focusing on NETs associated with Multiple Endocrine Neoplasia type 1 (MEN1). Aim To evaluate the efficacy of the long‐acting SSA octreotide in MEN1 patients with early‐stage duodeno‐pancreatic NETs. Patients and Methods Forty patients with MEN1 were retrospectively evaluated. Twenty patients with evidence of one or more MEN1‐related duodeno‐pancreatic NETs < 20 mm in size (age range 26–61 years) were treated with octreotide long‐acting octreotide (LAR) as first‐line therapy. Treatment duration ranged 12–75 months. At the baseline radiological evaluation, multiple duodeno‐pancreatic NETs (range 1–8, size 3–18 mm) were detected. Results An objective tumour response was observed in 10%, stable disease in 80% and progression of disease in 10% of cases. In six patients with abnormally increased CgA, gastrin and/or insulin serum concentrations, a significant clinical and hormonal response occurred in 100% of cases and was stable along the time. Conclusions Therapy with SSA is highly safe and effective in patients with early‐stage MEN1 duodeno‐pancreatic NETs, resulting in long‐time suppression of tumour and hormonal activity and 10% objective response. This suggests to early start therapy with SSA in patients with MEN1‐related NETs.